INFLUENCE OF 9 ELEMENTS OF JOURNALISM ON TEKNOKRA’S EDITORIAL POLICY - Toni Wijaya (Metakom, 2019)
The background of the research is the development of student journalism. Student newpaper has growth and massively popular among students as a source to keep in touch with university or student issue. Therefore a question emerged whether this kind of press implementing good journalism protocol ornot. The purpose of this research is to know the implementation of elements of journalism on student’s newspaper Teknokra. Teknokra had been chosen as object of research because they are the biggest student newpaper in Lampung University. The method used in this research is qualitative than the display using descriptive approach. Teknokra has been showing the decent level of consistency using elements of journalism protocol. The results showed decent determination from editorial leader dan its journalits on this issue because Teknokra viewed elements of journalism as a tools and guidance to elevate their quality of journalism. Keywords: Journalism, element of journalism, student newspaper, information, press.